Chemomodulating Effects of Flavonoids in Human Leukemia Cells - Sak, Katrin; Everaus, Hele (Anti-Cancer Agents in Medicinal Chemistry, 2015)
Flavonoids, a diverse class of polyphenolic compounds, are well known for their anticancer properties. Moreover, it is generally accepted that these plant secondary metabolites can also sensitize malignant cells to conventional chemotherapeutic drugs and could thus be considered as potential adjunctive agents in cancer treatment. In this review article we show that besides potentiating the anticancer activity of standard chemotherapeutics by modifying the molecular events that are involved in cell growth, differentiation and apoptosis, flavonoids might also act as inhibitory modulators in human leukemia cells. The specific behavior of a certain flavonoid in such combination treatments is multifactorial being dependent on various aspects, including cellular context, molecular mechanisms of clinical drugs, temporal regimen of administration, as well as doses of agents. Based on the highly complex nature of leukemogenesis it is feasible that a multifaceted therapeutic approach is also required to cure this disease and therefore, combined chemotherapeutic schemes incorporating natural plant metabolites as chemosensitizing agents can represent a new attractive strategy for more successful treatment of leukemia patients in the future. However, as highlighted in this review, caution should be taken when affecting malignant cells concurrently with chemotherapeutic drugs and flavonoids as unwisely chosen combinations can lead to inadvisable results and sometimes even deteriorate the clinical outcomes.
Keywords: leukemia cells